ACUAN TINGGI HILAL PERSPEKTIF NAHDLATUL ULAMA DAN MUHAMMADIYAH - Muhammad Syarief Hidayatullah (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
In Indonesia, there are two Islamic community organizations, Nahdlatul Ulama (NU) and Muhammadiyah. Hilal mar'i height reference held by these two organizations is different. In determining hilal mar’i height, NU is based on the disk under the moon, while the Muhammadiyah reference is on the moon's disk. This research becomes more interesting when looking at astronomical theory in general which explains that the moon will remain in the shape of a whole round disk regardless of any phase and when calculating the movement of the moon (altitude, azimuth, elongation, parallax, etc.) which will refer to the midpoint the moon disk. On the other hand, the differences in the reference to the hilal mar’i height perspective NU and Muhammadiyah have not been clearly described, and the basic reasons or theories underlying the use of the hilal hilal height reference. The legal basis used by NU and Muhammadiyah in relation to the hilal height reference refers to the syar'i propositions. However, differences in the definition of the new moon makes the two organizations have different ways of determining the beginning of the month.